2020
DOI: 10.1101/2020.01.14.904300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of phosphosites that alter protein thermal stability

Abstract: Proteomics has enabled the cataloguing of 100,000s of protein phosphorylation sites 1 , however we lack methods to systematically annotate their function. Phosphorylation has numerous biological functions, yet biochemically all involve changes in protein structure and interactions. These biochemical changes can be recapitulated by measuring the difference in stability between the protein and the phosphoprotein. Building on recent work, we present a method to infer phosphosite functionality by reliably measurin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has been shown that the ratio between peptide and stationary phase is critical to achieve good enrichment selectivity, 17 (phosphopeptides representing roughly 60% of the total peptides identified, while nowadays more than 90% specificity is routinely achieved-98% in our study) is thus an indication that the way the authors performed phosphopeptide enrichment is suboptimal. Further, the enrichment selectivity of Huang et al was variable from sample to sample, as analyzed in an accompanying work by Smith et al 18 . Importantly, the authors did not validate the linearity of enrichment capacity over a broad range of peptide amount input, and therefore this step might negatively influence their results by introducing quantification biases which will impact the estimation of phosphopeptide melting points-particularly, for an approach with low amount of TiO2 stationary phase (TiO2 spin tips used by the authors, catalog no.…”
Section: Peptide Labeling and Phosphopeptide Enrichmentmentioning
confidence: 99%
“…It has been shown that the ratio between peptide and stationary phase is critical to achieve good enrichment selectivity, 17 (phosphopeptides representing roughly 60% of the total peptides identified, while nowadays more than 90% specificity is routinely achieved-98% in our study) is thus an indication that the way the authors performed phosphopeptide enrichment is suboptimal. Further, the enrichment selectivity of Huang et al was variable from sample to sample, as analyzed in an accompanying work by Smith et al 18 . Importantly, the authors did not validate the linearity of enrichment capacity over a broad range of peptide amount input, and therefore this step might negatively influence their results by introducing quantification biases which will impact the estimation of phosphopeptide melting points-particularly, for an approach with low amount of TiO2 stationary phase (TiO2 spin tips used by the authors, catalog no.…”
Section: Peptide Labeling and Phosphopeptide Enrichmentmentioning
confidence: 99%
“…This reinforces our interpretation that for proteins with non-sigmoid behaviour, we are observing a mixture of behaviours from different functional copies of those proteins. This motivates expansion of the TPP method to deconvolute these behaviours, for example phosphoTPP (Huang et al ., 2019; Potel et al ., 2020; Smith et al ., 2020) and other PTMs. The RNA-binding behaviour could be examined with high-throughput RNA-protein enrichment methods (Queiroz et al ., 2019) and further deconvolution could be obtained by combining TPP with spatial proteomics methods (Mulvey et al ., 2017; Geladaki et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it can be applied to study interactions with metabolites, nucleotides and nucleic acids (Saei et al ., 2018; Dziekan et al ., 2019; Sridharan et al ., 2019; Becher et al ., 2018). Authors have shown that proteins in complex with each other are more likely to have concordant in vivo melting curves (Tan et al ., 2018) and others have demonstrated that phosphorylation can alter thermal stability (Huang et al ., 2019; Potel et al ., 2020; Smith et al ., 2020). Thermal proteome profiling has also been complemented with extensive structural analysis (Feng et al ., 2014; Leuenberger et al ., 2017; Schopper et al ., 2017; Piazza et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental approaches for high-throughput identification of protein phosphosite functions have been largely lacking. More recently, a promising approach has been to use a modified thermal proteome profiling (TPP) approach where the TPP protocol is conducted in conjunction with phosphoproteomics to identify functional phosphosites [18][19][20][21] . This method has proven useful to directly determine whether a phosphosite is likely to be functional or not.…”
Section: Introductionmentioning
confidence: 99%